Method for producing porous carbon, porous carbon, negative electrode material, and secondary battery

By using nanoscale carbon nanotubes in lithium-ion batteries to prepare porous carbon and introducing germanium or tin elements, the problems of low conductivity and low lithium activity of silicon-based materials are solved, and the performance and stability of lithium-ion batteries are improved.

CN119160873APending Publication Date: 2024-12-20CARBON ONE NEW ENERGY HANGZHOU CO LTD

Patent Information

Application Number
CN202411319473.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Silicon-based materials have problems with low conductivity and low lithium activity in the negative electrode applications of lithium-ion batteries, which affect the rate performance and cycle stability of the battery.

Method used

Porous carbon is prepared by nano-scale carbon nanotubes. Through the drying and carbonization process of phenolic resin microsphere suspension, porous carbon with high conductivity is formed, and a small amount of germanium or tin elements are introduced into the porous carbon to improve the deintercalation of lithium ions. efficiency.

Benefits of technology

It significantly improves the conductivity and lithium activity of silicon-based materials, improves the performance of lithium-ion batteries, reduces dead lithium residues, and improves the mechanical strength and electrical properties of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160873A_ABST
    Figure CN119160873A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of porous carbon, the porous carbon, a negative electrode material and a secondary battery, the preparation method of the porous carbon comprises the following steps: granulation: drying and granulating a phenolic resin microsphere suspension to obtain powder; nano carbon nanotubes are dispersed in the phenolic resin microspheres; and carbonization: sequentially carrying out secondary curing, pre-oxidation and carbonization on the powder to obtain the porous carbon. According to the preparation method, the porous carbon is prepared by adopting the nanoscale carbon nanotubes, firstly, the conductivity of the porous carbon is favorably improved due to the good conductivity of the carbon nanotubes, and meanwhile, the nanoscale carbon nanotubes are utilized, so that the carbon nanotubes can be more sufficiently dispersed, and the effect of improving the conductivity of the porous carbon by the carbon nanotubes is more favorably exerted; secondly, the tin or germanium element doped into the negative electrode material assists lithium ion deintercalation by reducing lithium ion transition energy barriers, so that the first effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a method for preparing porous carbon, porous carbon, a negative electrode material and a secondary battery. Background Art

[0002] As a high-performance negative electrode material for lithium-ion batteries, silicon-based materials have the advantages of high theoretical capacity (about 4200mAh / g, much higher than 372mAh / g of graphite) and low lithiation potential, but there are also some challenges, including low conductivity and low lithium activity.

[0003] Silicon-based materials have low electrical conductivity, which limits the diffusion rate of lithium ions and the efficiency of electron transfer, thus affecting the rate performance and cycle stability of the battery. Existing solutions include doping or coating with conductive materials to improve electrical conductivity, but directly doping conductive materials into silicon-based materials has limited effect on improving the electrical conductivity of silicon-based materials;

[0004] The low lithium activity of silicon-based materials is due to the large volume expansion and contraction they experience during the lithiation / delithiation process, which in turn leads to poor contact between the active material and the current collector.

[0005] Low conductivity and low lithium activity are two major challenges in the application of silicon-based materials in lithium-ion battery negative electrodes. How to effectively improve the conductivity and lithium activity of silicon-based materials and thus improve the performance of lithium-ion batteries is an urgent problem to be solved. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing porous carbon, porous carbon, negative electrode material and secondary battery, which are helpful to improve the conductivity of silicon-based materials.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a method for preparing porous carbon, comprising:

[0009] Granulation, drying and granulating the phenolic resin microsphere suspension to obtain a powder; the phenolic resin microspheres contain dispersed carbon nanotubes;

[0010] Carbonization: the powder is sequentially subjected to a second curing, pre-oxidation and carbonization to obtain the porous carbon.

[0011] In an optional embodiment, the carbon nanotubes have an average length of 20 nm to 50 nm and an average aspect ratio of 1.5 to 5;

[0012] and / or, in the phenolic resin microsphere suspension, the mass ratio of the carbon nanotubes to the total mass of the phenolic raw material and the aldehyde raw material is 1:(1.5-10);

[0013] And / or, a doping source is further dispersed in the phenolic resin microspheres, the doping source is at least one of a germanium source and a tin source, the germanium source is selected from at least one of orthogermanate, metagermanate, germanium dihydroxide and germanium tetrahydroxide, and the tin source is selected from at least one of tin chloride, tin nitrate and tin sulfate;

[0014] And / or, a doping source is also dispersed in the phenolic resin microspheres, and the mass ratio of the carbon nanotubes to the doping source in the phenolic resin microsphere suspension is (5-10):1.

[0015] In an optional embodiment, the preparation method of the phenolic resin microsphere suspension includes: mixing a dispersant, a doping source, a phenolic raw material, an aldehyde raw material and a catalyst with an aqueous solution dispersed with carbon nanotubes and heat-insulating the mixture to obtain a prepolymer solution;

[0016] The prepolymer solution is mixed with a curing agent for first curing to obtain the phenolic resin microsphere suspension.

[0017] Preferably, the preparation method of the phenolic resin microsphere suspension satisfies at least one of the following features AG:

[0018] A. the dispersant is selected from at least one of F127, PVA, PEG and sodium silicate;

[0019] B. the aldehyde raw material is selected from at least one of formaldehyde and furfural;

[0020] C. the phenolic raw material is selected from at least one of phenol and resorcinol, and the mass ratio of the phenolic raw material to the aldehyde raw material is 1:(0.8-1.2);

[0021] D. the catalyst is selected from at least one of sodium hydroxide and lithium hydroxide, and the total mass ratio of the catalyst to the phenolic raw material and the aldehyde raw material is 1:(25-35);

[0022] E. The holding time is 4h-6h, and the temperature is 75℃-85℃;

[0023] F. The curing agent is selected from at least one of hexamethylenetetramine and ammonia water, and the total mass ratio of the curing agent to the phenolic raw material and the aldehyde raw material is 1: (11-15);

[0024] G. The first curing temperature is 90℃-95℃, and the first curing time is 2h-8h.

[0025] In an optional embodiment, the method for preparing the aqueous solution dispersed with carbon nanotubes comprises: ultrasonically stirring a mixture of carbon nanotubes and water to obtain the aqueous solution dispersed with carbon nanotubes; the method for preparing the aqueous solution dispersed with carbon nanotubes satisfies at least one of the following features ac:

[0026] a. The ultrasonic frequency is 50Hz-70Hz; the stirring rate is 50rpm-200rpm; the ultrasonic stirring time is 30min-60min;

[0027] b. The solid content of the aqueous solution dispersed with carbon nanotubes is 0.1wt%-10wt%;

[0028] c. The carbon nanotubes are obtained by ball milling the carbon nanotube raw material. The ball milling parameters include: ball to material ratio of (20-50): 1, ball mill speed of 500rpm-2000rpm, and inert gas atmosphere.

[0029] In an optional embodiment, the mixed solution of the phenolic resin microsphere suspension and the water-soluble binder is spray-dried to obtain the powder, and the spray-drying parameters include: inlet air temperature of 160°C-200°C, outlet air temperature of 80°C-120°C, feed rate of 100mL / h-300mL / h, and centrifugal atomization disk speed of 23000rpm-27000rpm;

[0030] and / or, the water-soluble binder is selected from at least one of a water-soluble resin, starch, dextrin and polyvinyl alcohol;

[0031] And / or, the volume ratio of the phenolic resin microsphere suspension to the water-soluble binder is 1:(0.5-4).

[0032] In an optional embodiment, the second curing temperature is 100°C-140°C, and the second curing time is 1h-4h;

[0033] And / or, the pre-oxidation temperature is 280°C-320°C, the pre-oxidation time is 1h-5h, and the pre-oxidation heating rate is 1°C / min-5°C / min;

[0034] And / or, the carbonization temperature is 800°C-1000°C, the carbonization time is 4h-8h, and the carbonization heating rate is 4°C / min-6°C / min.

[0035] In an optional embodiment, the method further includes activating the porous carbon with an activator to obtain activated porous carbon, wherein the activation temperature is 700°C-1100°C, the activation time is 2h-30h, and the mass ratio of the porous carbon to the activator is 1:(0.5-4).

[0036] In a second aspect, the present invention provides a porous carbon prepared by the preparation method described in the above embodiment;

[0037] Preferably, the porous carbon satisfies at least one of the following ①-④:

[0038] ① The pore volume range is 0.3cm 3 / g-1.4cm 3 / g;

[0039] ②Specific surface area range is 800m 2 / g-2600m 2 / g;

[0040] ③Average pore size 1.65nm-3.02nm;

[0041] ④ Particle size D50 ranges from 4μm to 30μm

[0042] In a third aspect, the present invention provides a negative electrode material, comprising the porous carbon described in the aforementioned embodiment and silicon and / or carbon distributed on the porous carbon.

[0043] In a fourth aspect, the present invention provides a secondary battery comprising the negative electrode material described in the aforementioned embodiment.

[0044] The present invention has the following beneficial effects:

[0045] In the present invention, nano-scale carbon nanotubes are used to prepare porous carbon. First, the good electrical conductivity of carbon nanotubes helps to improve the electrical conductivity of porous carbon. At the same time, the size of carbon nanotubes has an important influence on the electrical conductivity of porous carbon. Under normal circumstances, increasing the length of carbon nanotubes can form a continuous conductive path, which is more conducive to improving the electrical conductivity of porous carbon, and at the same time, it is more conducive to improving the mechanical strength of porous carbon. However, longer carbon nanotubes are easy to agglomerate, and the dispersion stability is poor, which is not conducive to the uniform distribution of carbon nanotubes in the suspension, and then not conducive to the improvement of the electrical conductivity of porous carbon. Therefore, nano-scale carbon nanotubes are used in the present invention, which is more conducive to improving the electrical conductivity of porous carbon. In addition, the doping of a small amount of tin or germanium can promote the deintercalation of lithium ions, reduce dead lithium residues, and improve the first effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0047] Figure 1 This is the SEM image of the porous carbon material prepared in the example. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0049] An embodiment of the present invention provides a method for preparing porous carbon, comprising:

[0050] Granulation, drying and granulating the phenolic resin microsphere suspension to obtain a powder; the phenolic resin microspheres contain dispersed carbon nanotubes;

[0051] Carbonization: the powder is sequentially subjected to a second curing, pre-oxidation and carbonization to obtain the porous carbon.

[0052] In the embodiment of the present invention, nano-scale carbon nanotubes are used to prepare porous carbon. First, the good electrical conductivity of carbon nanotubes helps to improve the electrical conductivity of porous carbon. At the same time, the size of carbon nanotubes has an important influence on the electrical conductivity of porous carbon. Generally, increasing the length of carbon nanotubes can form a continuous conductive path, which is more conducive to improving the electrical conductivity of porous carbon and the mechanical strength of porous carbon. However, longer carbon nanotubes are easy to agglomerate and have poor dispersion stability, which is not conducive to the uniform distribution of carbon nanotubes in the suspension, and thus is not conducive to the improvement of the electrical conductivity of porous carbon. Therefore, the use of nano-scale carbon nanotubes in the present invention is more conducive to improving the electrical conductivity of porous carbon.

[0053] In an optional embodiment, the average length of the nano carbon nanotubes is 20nm-50nm, specifically 20nm, 30nm, 40nm, 50nm or any value between 20nm and 50nm; the average aspect ratio is 1.5-5, specifically 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or any value between 1.5-5.

[0054] When the size of the carbon nanotubes is within an appropriate range, it is beneficial for the carbon nanotubes to be wrapped by the phenolic resin microspheres. On the one hand, wrapping by the phenolic resin microspheres can inhibit the agglomeration of the carbon nanotubes, which is beneficial to improving the dispersion stability of the carbon nanotubes. On the other hand, if the size of the carbon nanotubes is too large, it is difficult to be wrapped by the phenolic resin microspheres, which may also affect the sphericity and pore structure of the subsequent porous carbon, thereby affecting the electrical properties of the negative electrode material prepared from the porous carbon.

[0055] In an optional embodiment, in the phenolic resin microsphere suspension, the mass ratio of carbon nanotubes to the total mass of phenolic raw materials and aldehyde raw materials is 1:(1.5-10), specifically 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10 or any value between 1:(1.5-10).

[0056] Although the introduction of carbon nanotubes into phenolic resin microspheres is beneficial to improve the electrical conductivity, if the amount is too much, it may reduce the uniformity of the carbon nanotube distribution, thereby affecting the electrical properties of the negative electrode material prepared from porous carbon.

[0057] In an optional embodiment, a doping source is also dispersed in the phenolic resin microspheres, and the doping source is at least one of a germanium source and a tin source, the germanium source is selected from at least one of orthogermanate, metagermanate, germanium dihydroxide and germanium tetrahydroxide, and the tin source is selected from at least one of tin chloride, tin nitrate and tin sulfate.

[0058] Introducing germanium or tin elements into porous carbon is beneficial to expanding the lattice size, which in turn is beneficial to further improving ionic conductivity, reducing energy barriers, making lithium deintercalation easier, and reducing the generation of dead lithium, thereby improving the primary efficiency of the silicon-carbon negative electrode. In addition, in this embodiment, introducing a doping source into the phenolic resin microspheres is more conducive to the uniform distribution of the doping source in the porous carbon.

[0059] In an optional embodiment, a doping source is also dispersed in the phenolic resin microspheres, and the mass ratio of the carbon nanotubes to the doping source in the phenolic resin microsphere suspension is (5-10):1, specifically 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value between (5-10):1.

[0060] Introducing a small amount of germanium or tin into porous carbon is more beneficial to the "local expansion" effect, which in turn is beneficial to the transport of Li ions. However, if the amount is too much, it may have the opposite effect, that is, the "narrow channel" effect dominates, which in turn increases the migration energy barrier of Li ions and increases the content of "dead lithium", thereby affecting the electrical properties of the negative electrode material prepared from porous carbon.

[0061] In an optional embodiment, the preparation method of the phenolic resin microsphere suspension includes: mixing a dispersant, a doping source, a phenolic raw material, an aldehyde raw material and a catalyst with an aqueous solution dispersed with carbon nanotubes and heat-insulating the mixture to obtain a prepolymer solution;

[0062] The prepolymer solution is mixed with a curing agent for first curing to obtain the phenolic resin microsphere suspension.

[0063] In the mixing step, the purpose of the dispersant is to promote uniform dispersion of carbon nanotubes and inhibit their agglomeration. Therefore, it is usually necessary to first add the dispersant into the aqueous solution, and then add the doping source, phenol raw material, aldehyde raw material and catalyst.

[0064] In this embodiment, a CNT uniformly dispersed aqueous solution is first obtained, and phenolic resin microspheres with carbon nanotubes as the core are polymerized in the uniformly dispersed CNT aqueous solution, which is more conducive to ensuring that the carbon nanotubes are wrapped by the phenolic resin microspheres.

[0065] Preferably, the preparation method of the phenolic resin microsphere suspension satisfies at least one of the following features AG:

[0066] A. the dispersant is selected from at least one of F127 (poloxamer 407), PVA (polyvinyl alcohol), PEG (polyethylene glycol) and sodium silicate;

[0067] B. the aldehyde raw material is selected from at least one of formaldehyde and furfural;

[0068] C. The phenolic raw material is selected from at least one of phenol and resorcinol, and the mass ratio of the phenolic raw material to the aldehyde raw material is 1:(0.8-1.2), specifically, it can be 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2 or any value between 1:(0.8-1.2);

[0069] D. the catalyst is selected from at least one of sodium hydroxide and lithium hydroxide, and the total mass ratio of the catalyst to the phenolic raw material and the aldehyde raw material is 1:(25-35), specifically 1:25, 1:27, 1:29, 1:31, 1:33, 1:35 or any value between 1:(25-35);

[0070] E. The holding time is 4h-6h, specifically 4h, 5h, 6h or any value between 4h-6h; the temperature is 75℃-85℃, specifically 75℃, 80℃, 85℃ or any value between 75℃-85℃;

[0071] F. The curing agent is selected from at least one of hexamethylenetetramine and ammonia water, and the total mass ratio of the curing agent to the phenolic raw material and the aldehyde raw material is 1:(11-15), specifically 1:11, 1:12, 1:13, 1:14, 1:15 or any value between 1:(11-15);

[0072] G. The first curing temperature is 90°C-95°C, specifically 90°C, 93°C, 95°C or any value between 90°C-95°C. The first curing time is 2h-8h, specifically 2h, 5h, 8h or any value between 2h-8h.

[0073] By selecting the raw materials and synthesis conditions for synthesizing the phenolic resin, the pore structure of the porous carbon is adjusted, wherein curing can make the cross-linked polymerized nanospheres become solid phenolic resin nanospheres.

[0074] In an optional embodiment, the method for preparing the aqueous solution dispersed with carbon nanotubes comprises: ultrasonically stirring a mixture of carbon nanotubes and water to obtain the aqueous solution dispersed with carbon nanotubes; the method for preparing the aqueous solution dispersed with carbon nanotubes satisfies at least one of the following features ac:

[0075] a. The ultrasonic frequency is 50Hz-70Hz, specifically 50Hz, 60Hz, 70Hz or any value between 50Hz-70Hz; the stirring rate is 50rpm-200rpm, specifically 50rpm, 100rpm, 150rpm, 200rpm or any value between 50rpm-200rpm; the ultrasonic stirring time is 30min-60min, specifically 30min, 40min, 50min, 60min or any value between 30min-60min, and ultrasound and stirring are carried out simultaneously, which is beneficial to the dispersion of carbon nanotubes and maintaining the stability of the aqueous solution.

[0076] b. The solid content of the aqueous solution dispersed with carbon nanotubes is 0.1wt%-10wt%, specifically 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value between 0.1wt% and 10wt%, which is beneficial to the dispersion of carbon nanotubes and maintaining the stability of the aqueous solution.

[0077] c. The nano carbon nanotubes are obtained by ball milling the carbon nanotube raw material, and the ball milling parameters include: the ball-to-material ratio is (20-50):1, specifically 20:1, 30:1, 40:1, 50:1 or any value between (20-50):1, the ball mill speed is 500rpm-2000rpm, specifically 500rpm, 1000rpm, 1500rpm, 2000rpm or any value between 500rpm-2000rpm, and the gas is an inert gas atmosphere. First, the carbon nanotube raw material is ball milled to obtain nano carbon nanotubes of suitable particle size, which is beneficial to improve the uniformity and stability of the dispersion of the nano carbon nanotubes in the aqueous solution, and is more conducive to the subsequent encapsulation of the carbon nanotubes during the synthesis of phenolic resin.

[0078] In an optional embodiment, the mixed solution of the phenolic resin microsphere suspension and the water-soluble binder is spray-dried to obtain the powder, and the spray-drying parameters include: an air inlet temperature of 160°C-200°C, specifically 160°C, 170°C, 180°C, 190°C, 200°C or any value between 160°C and 200°C, and an air outlet temperature of 80°C-120°C, specifically 80°C, 90°C, 100°C, 110°C, 120°C or 80°C-1 20 ℃, the feed rate is 100mL / h-300mL / h, specifically 100mL / h, 200mL / h, 300mL / h or any value between 100mL / h-300mL / h, the speed of the centrifugal atomization disk is 23000rpm-27000rpm, specifically 23000rpm, 25000rpm, 27000rpm or any value between 23000rpm-27000rpm.

[0079] Spray drying can achieve drying and granulation at the same time, which is beneficial to improving efficiency. In addition, spray drying is beneficial to improving the sphericity of the powder, and then to improving the sphericity of the finally prepared porous carbon.

[0080] In an optional embodiment, the water-soluble binder is selected from at least one of a water-soluble resin, starch, dextrin and polyvinyl alcohol;

[0081] And / or, the volume ratio of the phenolic resin microsphere suspension to the water-soluble binder is 1:(0.5-4), specifically 1:0.5, 1:1, 1:2, 1:3, 1:4 or any value in between 1:(0.5-4).

[0082] The addition of binder can adjust the slurry viscosity to a reasonable range suitable for spray drying. In addition, the amount and type of water-soluble binder will affect the particle size of the powder and the pore structure of porous carbon.

[0083] In an optional embodiment, the second curing temperature is 100°C-140°C, specifically 100°C, 110°C, 120°C, 130°C, 140°C or any value between 100°C-140°C, and the second curing time is 1h-4h, specifically 1h, 2h, 3h, 4h or any value between 1h-4h;

[0084] On the one hand, this curing can reduce the water content of the material, and on the other hand, it is beneficial to increase the degree of cross-linking of the resin, thereby affecting the pore structure, thermal stability and mechanical strength of the porous carbon.

[0085] In an optional embodiment, the pre-oxidation temperature is 280°C-320°C, specifically 280°C, 290°C, 300°C, 310°C, 320°C or any value between 280°C and 320°C, the pre-oxidation time is 1h-5h, specifically 1h, 2h, 3h, 4h, 5h or any value between 1h-5h, the pre-oxidation heating rate is 1°C / min-5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min-5°C / min; at the pre-oxidation temperature, the degree of resin cross-linking is further improved, thereby further improving the stability of the porous carbon and forming more porous structures.

[0086] In an optional embodiment, the carbonization temperature is 800°C-1000°C, specifically 800°C, 900°C, 1000°C or any value between 800°C and 1000°C, the carbonization time is 4h-8h, specifically 4h, 5h, 6h, 7h, 8h or any value between 4h-8h, and the carbonization heating rate is 4°C / min-6°C / min, specifically 4°C / min, 5°C / min, 6°C / min or any value between 4°C / min and 6°C / min.

[0087] During the carbonization process, the organic components in the phenolic resin are decomposed, leaving a carbon skeleton and forming porous carbon, among which a higher pyrolysis temperature is conducive to the production of a more stable carbon skeleton and a more developed pore structure.

[0088] In an optional embodiment, the method further includes activating the porous carbon with an activator to obtain activated porous carbon, wherein the activation temperature is 700°C-1100°C, specifically 700°C, 800°C, 900°C, 1000°C, 1100°C or any value between 700°C and 1100°C, the activation time is 2h-30h, specifically 2h, 5h, 10h, 15h, 20h, 25h, 30h or any value between 2h and 30h, and the mass ratio of the porous carbon to the activator is 1:(0.5-4), specifically 1:0.5, 1:1, 1:2, 1:3, 1:4 or any value between 1:(0.5-4).

[0089] The activation step can affect the pore structure and specific surface area of ​​porous carbon, which is beneficial to improve the performance of the negative electrode material prepared therefrom. Among them, the activator is divided into physical activators and chemical activators. The physical activators are common CO2, water, etc., and the chemical activators are KOH, NaOH, phosphoric acid, etc.

[0090] The embodiment of the present invention further provides a porous carbon, which is prepared by the preparation method described in the above embodiment;

[0091] Preferably, the porous carbon satisfies at least one of the following ①-④:

[0092] ① The pore volume range is 0.3cm 3 / g-1.4cm 3 / g;

[0093] ②Specific surface area range is 800m 2 / g-2600m 2 / g;

[0094] ③Average pore size 1.65nm-3.02nm;

[0095] ④ The particle size D50 ranges from 4μm to 30μm.

[0096] Porous carbon meets the above requirements and is beneficial to improving the performance of the negative electrode material prepared therefrom.

[0097] An embodiment of the present invention further provides a negative electrode material, comprising the porous carbon described in the foregoing embodiment and silicon and / or carbon distributed on the porous carbon.

[0098] In some embodiments, the prepared porous carbon is placed in a deposition furnace for CVD vapor deposition to obtain a silicon-carbon material, the furnace temperature is 400°C-800°C, the silicon source is one or two of monosilane, disilane, and trichlorosilane, and the silane deposition time is 2h-12h; after the deposition is completed, a carbon source is introduced for vapor coating, wherein the carbon source is one or two of methane, acetylene, and ethylene, and the thickness of the carbon coating layer is 1-10nm. For the final silicon-carbon negative electrode material, the mass ratio of the carbon coating layer is 1-5%, and the mass ratio of the nano-silicon particles is 30%-80%.

[0099] An embodiment of the present invention further provides a secondary battery, comprising the negative electrode material described in the above embodiment.

[0100] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0101] Example 1

[0102] This embodiment provides a method for preparing a negative electrode material, which specifically includes the following steps:

[0103] 1) 20 g CNT and 400 g zirconium balls were placed in a ball mill to make four groups, where the ball milling speed was 1500 rpm and the ball milling time was 20 h. After the four groups were evenly mixed, they were sieved to obtain CNT particles with an average length of 20-50 nm and an average aspect ratio of 2.

[0104] 2) 27 g of the ball-milled CNT particles were put into 500 mL of deionized water for ultrasonic stirring and dispersion. The ultrasonic frequency was set to 60 Hz, the ultrasonic time was 40 min, and the stirring rate was 150 rpm. After the ultrasonication, a CNT dispersion aqueous solution with a solid content of 5% was obtained.

[0105] 3) 0.5 g F127, 3 g germanium dihydroxide, 21.5 g phenol, 23.5 g formaldehyde and 1.5 g sodium hydroxide were sequentially added to the CNT dispersion aqueous solution for oil bath treatment at an oil bath temperature of 80° C. After keeping the temperature for 4 hours, a precursor solution was obtained;

[0106] 4) Add 3.5 g of hexamethylenetetramine to the precursor solution, raise the temperature of the oil bath to 95° C., and then keep the temperature for 6 hours to obtain a phenolic resin microsphere suspension.

[0107] 5) Mix a water-soluble resin binder (water-soluble thermosetting phenolic resin liquid) and a phenolic resin microsphere suspension in a ratio of 1:1, stir with a homogenizer for 1 hour, and then spray dry. The spray drying setting parameters are: inlet air temperature 180°C, outlet air temperature 90°C, feed rate 100ml / h, and centrifugal atomizer speed 25000rpm.

[0108] 6) Collect the powder in the spray drying aggregate bottle, place the powder in an oven at 120°C for curing for 2 hours, and then heat it in a muffle furnace at a heating rate of 3°C / min from room temperature to 300°C for 2 hours for pre-oxidation treatment.

[0109] 7) The pre-oxidized powder is placed in a tubular furnace for carbonization treatment. Nitrogen is introduced into the tubular furnace, and the temperature is increased from room temperature to 800°C at a heating rate of 5°C / min and maintained for 4 hours to obtain spherical carbon.

[0110] 8) The spherical carbon and KOH were placed in a tube furnace at a ratio of 1:2.5 and activated at 950°C for 3 h to obtain spherical porous carbon. The SEM image is shown in Figure 1 .

[0111] 9) The spherical porous carbon is placed in a CVD furnace, and methane and monosilane are vapor deposited in a ratio of 1:3 to obtain a spherical silicon-based negative electrode material.

[0112] Example 2

[0113] This embodiment provides a method for preparing a negative electrode material, which is different from Embodiment 1 only in that in step 1), germanium dihydroxide is replaced by tin chloride.

[0114] Example 3

[0115] This embodiment provides a method for preparing a negative electrode material, which is different from Embodiment 1 only in that step 2) shortens the ultrasonic time to 30 min.

[0116] Example 4

[0117] This embodiment provides a method for preparing a negative electrode material, which is different from Embodiment 1 only in that in step 5), the feed rate is increased to 300 ml / h.

[0118] Example 5

[0119] This embodiment provides a method for preparing a negative electrode material, which is different from Embodiment 1 only in that, in step 8), the ratio of spherical carbon to KOH is adjusted to 1:1.

[0120] Comparative Example 1

[0121] This comparative example provides a method for preparing a negative electrode material, which is different from Example 1 only in that step 1) is omitted and CNT is not added in step 2).

[0122] Comparative Example 2

[0123] This comparative example provides a method for preparing a negative electrode material, which is different from Example 1 only in that no germanium source is added in step 3).

[0124] Comparative Example 3

[0125] This comparative example provides a method for preparing a negative electrode material, which is different from Example 1 only in that step 2) is omitted and 27 g of CNT particles in step 1) are added in step 5).

[0126] Comparative Example 4

[0127] This comparative example provides a method for preparing a negative electrode material, which is different from Example 1 only in that step 1) is omitted.

[0128] Comparative Example 5

[0129] This comparative example provides a method for preparing a negative electrode material, which differs from Example 1 only in that steps 3-4) are cancelled, and step 5) is modified to take the CNT dispersed aqueous solution in step 2) and the water-soluble thermosetting phenolic resin liquid in a 1:1 ratio and stir it with a homogenizer for 1 hour before spray drying. The spray drying setting parameters are as follows: an inlet air temperature of 180°C, an outlet air temperature of 90°C, a feed rate of 100ml / h, and a centrifugal atomizer speed of 25000rpm.

[0130] The negative electrode materials obtained in the above embodiments and comparative examples were tested, and the negative electrode materials obtained in the above embodiments and comparative examples were assembled into batteries. The specific steps are as follows: (1) Preparation of electrode sheets: first, the active material, binder, and conductive carbon black were placed in a mortar in a ratio of 8:1:1, and 5-8 drops of N-methylpyrrolidone were added to make a slurry. The slurry was coated on a copper foil, then placed in a vacuum oven at 80°C for 8 hours, and then sliced ​​to obtain an electrode sheet. (2) Button battery assembly: The negative electrode shell, lithium sheet, 3-4 drops of electrolyte, PF porous polymer separator, 3-4 drops of electrolyte, electrode sheet, and positive shell were assembled into a half-cell in sequence. The electrolyte here is a liquid composed of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M). The battery was tested at 25°C. The specific steps were as follows: first, discharge at 0.1C to 0.005V, then discharge at 0.08C to 0.001V, then discharge at 0.05C to 0.001V, then discharge at 0.02C to 0.001V, and let stand for 10 minutes; then charge at 0.1C to 1.5V, let stand for 10 minutes, record the charge capacity after the first cycle, and calculate the first coulombic efficiency. The results are shown in Table 2.

[0131] Table 1

[0132]

[0133] Table 2

[0134]

[0135]

[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing porous carbon, characterized in that: include: Granulation, drying and granulating the phenolic resin microsphere suspension to obtain a powder; The phenolic resin microspheres are dispersed with carbon nanotubes; Carbonization: the powder is sequentially subjected to a second curing, pre-oxidation and carbonization to obtain the porous carbon.

2. The method for preparing porous carbon according to claim 1, characterized in that: The carbon nanotubes have an average length of 20nm-50nm and an average aspect ratio of 1.5-5; and / or, in the phenolic resin microsphere suspension, the mass ratio of the carbon nanotubes to the total mass of the phenolic raw material and the aldehyde raw material is 1:(1.5-10); And / or, a doping source is further dispersed in the phenolic resin microspheres, the doping source is at least one of a germanium source and a tin source, the germanium source is selected from at least one of orthogermanate, metagermanate, germanium dihydroxide and germanium tetrahydroxide, and the tin source is selected from at least one of tin chloride, tin nitrate and tin sulfate; And / or, a doping source is also dispersed in the phenolic resin microspheres, and the mass ratio of the carbon nanotubes to the doping source in the phenolic resin microsphere suspension is (5-10):

1.

3. The method for preparing porous carbon according to claim 2, characterized in that: The preparation method of the phenolic resin microsphere suspension comprises: mixing a dispersant, a doping source, a phenolic raw material, an aldehyde raw material and a catalyst with an aqueous solution dispersed with nano carbon nanotubes and heat-insulating the mixture to obtain a prepolymer solution; The prepolymer solution is mixed with a curing agent for first curing to obtain the phenolic resin microsphere suspension; Preferably, the preparation method of the phenolic resin microsphere suspension satisfies at least one of the following features AG: A. the dispersant is selected from at least one of F127, PVA, PEG and sodium silicate; B. the aldehyde raw material is selected from at least one of formaldehyde and furfural; C. the phenolic raw material is selected from at least one of phenol and resorcinol, and the mass ratio of the phenolic raw material to the aldehyde raw material is 1:(0.8-1.2); D. the catalyst is selected from at least one of sodium hydroxide and lithium hydroxide, and the total mass ratio of the catalyst to the phenolic raw material and the aldehyde raw material is 1:(25-35); E. The holding time is 4h-6h, and the temperature is 75℃-85℃; F. The curing agent is selected from at least one of hexamethylenetetramine and ammonia water, and the total mass ratio of the curing agent to the phenolic raw material and the aldehyde raw material is 1: (11-15); G. The first curing temperature is 90℃-95℃, and the first curing time is 2h-8h.

4. The method for preparing porous carbon according to claim 3, characterized in that: The method for preparing the aqueous solution dispersed with nano-carbon nanotubes comprises: ultrasonically stirring a mixture of nano-carbon nanotubes and water to obtain the aqueous solution dispersed with nano-carbon nanotubes; the method for preparing the aqueous solution dispersed with nano-carbon nanotubes satisfies at least one of the following features ac: a. Ultrasonic frequency is 50Hz-70Hz; stirring rate is 50rpm-200rpm; ultrasonic stirring time is 30min-60min; b. The solid content of the aqueous solution dispersed with carbon nanotubes is 0.1wt%-10wt%; c. The carbon nanotubes are obtained by ball milling the carbon nanotube raw material. The ball milling parameters include: ball to material ratio of (20-50): 1, ball mill speed of 500rpm-2000rpm, and inert gas atmosphere.

5. The method for preparing porous carbon according to claim 1, characterized in that: The mixed solution of the phenolic resin microsphere suspension and the water-soluble binder is spray-dried to obtain the powder, wherein the spray-drying parameters include: an air inlet temperature of 160° C.-200° C., an air outlet temperature of 80° C.-120° C., a feed rate of 100 mL / h-300 mL / h, and a centrifugal atomizing disk speed of 23000 rpm-27000 rpm; and / or, the water-soluble binder is selected from at least one of a water-soluble resin, starch, dextrin and polyvinyl alcohol; And / or, the volume ratio of the phenolic resin microsphere suspension to the water-soluble binder is 1:(0.5-4).

6. The method for preparing porous carbon according to claim 1, characterized in that: The second curing temperature is 100℃-140℃, and the second curing time is 1h-4h; And / or, the pre-oxidation temperature is 280°C-320°C, the pre-oxidation time is 1h-5h, and the pre-oxidation heating rate is 1°C / min-5°C / min; And / or, the carbonization temperature is 800°C-1000°C, the carbonization time is 4h-8h, and the carbonization heating rate is 4°C / min-6°C / min.

7. The method for preparing porous carbon according to claim 1, characterized in that: The method also includes activating the porous carbon with an activator to obtain activated porous carbon, wherein the activation temperature is 700°C-1100°C, the activation time is 2h-30h, and the mass ratio of the porous carbon to the activator is 1:(0.5-4).

8. A porous carbon, characterized in that Prepared by the preparation method according to claim 1; Preferably, the porous carbon satisfies at least one of the following ①-④: ① The pore volume range is 0.3cm 3 / g-1.4cm 3 / g; ②Specific surface area range is 800m 2 / g-2600m 2 / g; ③Average pore size 1.65nm-3.02nm; ④ The particle size D50 ranges from 4μm to 30μm.

9. A negative electrode material, characterized in that: The porous carbon comprises the porous carbon as claimed in claim 1 and silicon and / or carbon distributed on the porous carbon.

10. A secondary battery, characterized in that: Comprising the negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of phenolic resin-based hard carbon microsphere material

    CN113321202A

  • Germanium-doped silicon-like negative electrode material as well as preparation method and application thereof

    CN113659124A

  • Preparation method of heteroatom-doped silicon-carbon negative electrode material and material thereof

    CN114566637A

  • Silicon-carbon negative electrode material, negative electrode plate and secondary battery

    CN117174862A

  • Silicon-carbon composite material and preparation method therefor, and secondary battery comprising same

    WO2024040615A1

Cited By

  • Spherical porous carbon as well as preparation method and application thereof

    CN119976806A

  • A spherical porous carbon, its preparation method and application

    CN119976806B

  • Preparation method of high-conductivity resin-based porous carbon material with porous carbon skeleton

    CN121536924A

  • Process for the preparation of a highly conductive resin-based porous carbon material having a porous carbon skeleton

    CN121536924B

  • Carbon material, silicon-carbon negative electrode material, and preparation method for and use of silicon-carbon negative electrode material

    EP4759772A2